Draft genome sequences and resistome analysis of multidrug-resistant mcr-1-harbouring Escherichia coli isolated from pre-harvest poultry in Lebanon. (June 2021) - Kassem, Issmat I.; Mann, David; Li, Shaoting; Deng, Xiangyu
Highlights: Whole-genome sequencing analysis of mcr-1- positive Escherichia coli from poultry in Lebanon. The strains were found to carry 9–19 antimicrobial resistance genes. mcr-1.1 was found to be carried on an IncX4 plasmid in the majority of sequenced isolates. ABSTRACT: Objectives: Antibiotic resistance poses a serious risk in Lebanon, a country with challenges in infrastructure and antibiotic stewardship. Recently, a high prevalence of multidrug-resistant (MDR) Escherichia coli harbouring the mobile colistin resistance gene mcr-1 was reported in faecal matter of poultry in Lebanon. Some of the isolates also exhibited resistance to important antibiotics, including cephalosporins and carbapenems. We performed whole-genome sequencing (WGS) to analyse the genetic determinants of resistance and the sequence types (ST) of five of the isolates. Methods: WGS was performed using a MiSeq sequencer. Draft genomes were assembled using SPAdes v.3.9.0. ResFinder v.3.0 and PlasmidFinder v.1.3 databases were used to analyse the acquired resistome and plasmid types, respectively. STs were determined using MLST software. Results: WGS analysis revealed that the strains harboured 9–19 antibiotic resistance genes, including mcr-1.1 and other genes encoding resistance to important antibiotics used in agriculture and human medicine. In each strain, mcr-1.1 was located on the same contig with IncX4 plasmid sequences. Furthermore, the strains belonged to different STs, including those associated with (i) zoonotic transmission from poultry to humans, (ii) food contamination and (iii) clinical samples. Conclusion: Our analysis revealed diverse genetic resistance determinants in MDR mcr-1 -positive E. coli from poultry in Lebanon. Furthermore, these strains belonged to STs associated with transmission to humans. Taken together, the occurrence of strains harbouring resistance to critical antibiotics in Lebanese poultry and their potential transmission to humans emphasize an urgent need to mitigate the dissemination of antibiotic resistance on poultry farms in Lebanon.